2017
DOI: 10.1021/acsomega.7b01165
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Decarboxylative Coupling of Alkynyl Carboxylic Acids with Aryl Tosylates

Abstract: Decarboxylative coupling reactions of alkynyl carboxylic acids with aryl tosylates were developed in the presence of a palladium catalyst. Among the commercially available phosphine ligands, only 1-dicyclohexylphosphino-2-(di- tert –butylphosphino-ethyl)ferrocene (CyPF- t Bu) showed good reactivity. The reaction took place smoothly and gave the decarboxylative coupled products in moderate to good yields. This demonstrates the excellent functional group tolerance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Song and Lee demonstrated a catalyst system of Pd(PPh 3 )Cl 2 / CyPF t ‐Bu and Cs 2 CO 3 for the coupling of alkynyl carboxylic acids and aryl tosylates (Figure 6). [ 140 ] Competitive coupling experiments were carried out with aryl halides/ tosylates. It was found that phenyl tosylates were less active than aryl iodides and bromides, but they were more active than aryl chlorides in this decarboxylative Sonogashira coupling.…”
Section: Sonogashira‐related Coupling Reactionsmentioning
confidence: 99%
“…Song and Lee demonstrated a catalyst system of Pd(PPh 3 )Cl 2 / CyPF t ‐Bu and Cs 2 CO 3 for the coupling of alkynyl carboxylic acids and aryl tosylates (Figure 6). [ 140 ] Competitive coupling experiments were carried out with aryl halides/ tosylates. It was found that phenyl tosylates were less active than aryl iodides and bromides, but they were more active than aryl chlorides in this decarboxylative Sonogashira coupling.…”
Section: Sonogashira‐related Coupling Reactionsmentioning
confidence: 99%
“…Spectroscopic data for catalysts and reaction products as well as additional references (Ref. [23,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]).…”
Section: Supporting Informationmentioning
confidence: 99%
“…The electrophilic cross‐coupling reactions catalyzed by dual nickel/palladium have been achieved between two different electrophiles (Figure 1A), primarily encompassing the following types:1) C(sp 2 )−Br and C(sp 2 )−OTf (aryl bromides and aryl triflates); [6a] 2) C(sp 2 )−Cl and C(sp 2 )−OTf (aryl chlorides and aryl triflates); [6b] 3) C(sp 2 )−OTs and C(sp 2 )−OTf (aryl tosylates and aryl triflates [6c,d] as well as between gem ‐difluorovinyltosylate and aryl triflates or cyclic vinyl triflates [6e] ); 4) C(sp 2 )−Br and C(sp 2 )−OTs (aryl bromides and 2,2‐difluorovinyl tosylates) [6f] . In comparison to aryl halides, aryl tosylates can be easily obtained from phenols, making them more appealing due to the abundance of phenols [8a,b] . However, there has been limited research on cross‐electrophile coupling reactions involving aryl tosylates due to their high stability [8] .…”
Section: Introductionmentioning
confidence: 99%